ZnO nanoarrays via a thermal decomposition–deposition method for sensitive and selective NO2 detection. Issue 20 (4th May 2021) - Lou, Chengming; Wang, Kai; Mei, Houshan; Xie, Jiayue; Zheng, Wei; Liu, Xianghong; Zhang, Jun
Abstract : ZnO nanoarrays deposited by a thermal decomposition–deposition (TDD) strategy demonstrate a high response for NO2 detection. Abstract : Metal oxide semiconductor (MOS) nanoarrays are excellent candidates as the sensing layers in electronic gas sensors as a result of their high surface-to-volume ratio and loose structure compared with particle-aggregated films. In this work, we develop a simple yet efficient in situ thermal decomposition–deposition (TDD) strategy that is capable of growing ZnO nanoarrays for mass production of gas sensors. The ZnO nanoarrays are self-assembled as ZnO nanowires with a preferential growth direction of (002). Gas sensing measurements reveal that the sensors based on ZnO nanoarrays exhibit remarkable sensitivity and selectivity toward NO2 detection at a low operating temperature of 140 °C. The ZnO sensor displays very high response ( R g / R a = 85) and fast response (6 s) and recovery (30 s) times for 10 ppm NO2, as well as a low limit of detection of 14 ppb. In addition, the sensor also possesses a notable humidity-resistant response. When the relative humidity increases from 60% to 85%, the sensor response is slightly decreased by 11.8% (from 85 to 75). The facile synthesis strategy and the ZnO nanoarray structure developed in this work are highly promising for practical sensor applications owing to the low fabrication cost and attractive anti-humidity sensing performance.